2016
DOI: 10.1136/bmjopen-2015-009911
|View full text |Cite
|
Sign up to set email alerts
|

Trauma teams and time to early management during in situ trauma team training

Abstract: ObjectivesTo investigate the association between the time taken to make a decision to go to surgery and gender, ethnicity, years in profession, experience of trauma team training, experience of structured trauma courses and trauma in the trauma team, as well as use of closed-loop communication and leadership styles during trauma team training.DesignIn situ trauma team training. The patient simulator was preprogrammed to represent a severely injured patient (injury severity score: 25) suffering from hypovolemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Hospital trauma care systems varied across the participating countries. The hospital trauma team, trauma protocol and education are the key elements of high‐quality trauma care . HICs have specialised trauma teams and trauma surgeons, while LMICs do not .…”
Section: Discussionmentioning
confidence: 99%
“…Hospital trauma care systems varied across the participating countries. The hospital trauma team, trauma protocol and education are the key elements of high‐quality trauma care . HICs have specialised trauma teams and trauma surgeons, while LMICs do not .…”
Section: Discussionmentioning
confidence: 99%
“…Every physician team leader carries the responsibility for their team's teamwork, because arguably a key purpose of instituting a physician team leader is to ensure good teamwork in ad-hoc teams. Given the complexity of leadership [3,10,12,13,49], particularly in highly dynamic environments such as emergency rooms, leaders may be operating at their full capacity and lack the necessary mental resources for additional meta-cognitive tasks such as selfmonitoring. The diffusion of responsibility observable even in small groups [50,51] may also lead to this diffused responsibility being burdened on the team leader when teams institute such a function explicitly, resulting in further leader overload.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive focus on the relationship between closed loop communication and patient safety in medicine, Härgestam (2013) found that closed loop communication was rarely used during trauma team training, even in high performing teams [17]. In addition, closed loop communication initiated by a team member rather than by the team leader could lead to communication overload [47]. Online commentaries are closely related to utterances that are termed “information-related talking to the room”, which refers to interpreting and sharing information that is associated with the further use of information-related talking to the room in high-performing anaesthesia teams [48].…”
Section: Discussionmentioning
confidence: 99%